A micro lead-based solid non-polarizable electrode and preparation method thereof
The challenges of electrodes in long-term use and miniaturization are solved by using electrolyte slurry of nanoscale vapor phase silica gel liquid and polypropylene separator in non-polarized electrodes, combined with a shell and a fixed cap made by 3D printing. Achieve high-precision and stable micro-lead-system solid non-polarized electrodes.
Patent Information
- Application Number
- CN202011261605.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-11-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-11-12
AI Technical Summary
Existing non-polarized electrodes are prone to changes in electrolyte concentration during long-term use, resulting in the inability to guarantee stability and difficult to meet long-term observation needs. At the same time, their miniaturization is difficult to be suitable for indoor simulation experiments.
The electrolyte slurry is prepared using nano-level vapor-phase silica gel liquid and components such as PbCl2, HCl, NaCl, etc., and the shell is divided into upper cavity and lower cavity through a polypropylene separator to avoid the problem of concentrated electrolyte components, and at the same time, 3D is used. Printed polypropylene shell and fixing cap to enhance the structural stability of the electrode.
The long-term stability and high precision of the electrode are achieved, suitable for indoor miniaturization simulation conditions, and solve the shortcomings of existing electrodes in terms of stability and miniaturization.
Smart Images

Figure CN112285783B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrodes, and in particular to a miniature lead-based solid non-polarizable electrode and a preparation method thereof. Background Art
[0002] Geophysical exploration refers to the detection of geological conditions such as stratum lithology and geological structure by studying and observing the changes in various geophysical fields. Since different rock media in the crust often differ in density, elasticity, conductivity, magnetism, radioactivity, and thermal conductivity, the above differences will cause local changes in the corresponding geophysical fields. By measuring the distribution and change characteristics of these physical fields and combining them with known geological data for analysis and research, the purpose of inferring geological properties can be achieved. This method has both exploration and testing functions. Compared with drilling, it has the advantages of light equipment, low cost, high efficiency, and wide working space, which is of great significance to human production and construction.
[0003] The most widely used exploration method in existing geophysical exploration is magnetotelluric sounding (MT), which mainly studies the electrical structure of the earth by measuring the change of potential difference in the earth and using the natural alternating electromagnetic field; therefore, the exploration of electrodes for measuring potential difference has become a top priority in this regard. Since metal electrodes will inevitably polarize during use, it is difficult to conduct long-term stable observations, so the electrodes currently used are mainly non-polarized electrodes formed by the reaction of metals and metal salt solutions.
[0004] At present, the production of non-polarizable electrodes usually involves inserting a metal wire into an electrode shell filled with a saturated metal salt solution, and contacting the soil through the bottom; the non-polarizable electrodes on the market mainly include Cu-CuSO4 electrodes, Pb-PbCl2 electrodes, and Ag-AgCl electrodes, etc. Among them, the most commonly used is the Pb-PbCl2 non-polarizable electrode, which is suitable for the observation of short-term, high-intensity geoelectric field signals, but cannot meet the long-term observation of geoelectric field signals. The production of non-polarizable electrodes usually involves inserting a metal wire into an electrode shell filled with a saturated metal salt solution, and contacting the soil through the bottom. The reason is that after a period of use, the electrolyte concentration of the non-polarizable electrode changes too much locally, and the stability cannot be guaranteed, and the electrolyte solution needs to be reconfigured. Therefore, the currently commonly used non-polarizable electrodes add excess salt and clay as fillers to the electrolyte solution to increase the saturation time of the electrode quality during use, which is called a solid non-polarizable electrode. For example, the invention of patent number CN201410795698.0 introduces a new Pb-PbCl2 solid electrode using kaolin as a viscous substance and NaCl, HCl, etc. as mixed electrolytes; its stability time can be up to about half a year, which solves its stability problem to a certain extent; however, due to the unstable composition of kaolin, the sedimentation of its internal solute will also affect the stability of the electrode.
[0005] In addition, due to certain difficulties in field research, most theoretical and simulation experiments are mainly completed in the form of small-scale indoor simulation experiments; therefore, the miniaturization of non-polarized electrodes has also become a key direction for in-depth research on magnetotelluric problems. The advantage of miniature non-polarized electrodes is that they are more suitable for indoor model simulations. Since the measurement time in indoor simulations is shorter, only 6 to 36 hours is required, the overall time cost is lower and the accuracy is higher. Although the invention of patent number CN201620184257.1 prepares electrodes that can be used for a long time, the internal Pb 2+ The composition variation between the upper and lower parts poses a great problem in the accuracy of the electrode and is difficult to use for small electrodes. Summary of the invention
[0006] In view of the above problems existing in the prior art, the present invention provides a miniature lead-based solid non-polarizable electrode and a preparation method thereof.
[0007] The invention discloses a miniature lead-based solid non-polarizable electrode, comprising: a shell;
[0008] The middle part of the shell is divided into an upper cavity and a lower cavity by a diaphragm, and the upper cavity and the lower cavity are both filled with electrolyte slurry;
[0009] A fixing cap is provided on the top of the shell, and an anode wire is passed through the fixing cap. One end of the anode wire extends into the electrolyte slurry of the upper cavity, and the other end is connected to an external wire.
[0010] A wooden bottom plate is provided at the bottom of the shell, and the electrolyte slurry in the lower cavity is in contact with the external environment through the wooden bottom plate.
[0011] As a further improvement of the present invention, the diaphragm is a polypropylene diaphragm with uniform pores.
[0012] As a further improvement of the present invention, the shell and the fixing cap are both polypropylene components made by 3D printing.
[0013] As a further improvement of the present invention, the fixing cap is provided with a wiring hole for the anode wire to pass through, and the anode wire is sealed on the wiring hole by organic silicone.
[0014] As a further improvement of the present invention, the wiring hole is a long wiring hole with a preset length.
[0015] As a further improvement of the present invention, the anode wire is a lead wire, the conducting wire is a copper conducting wire, and the other end of the conducting wire is connected to a testing instrument.
[0016] As a further improvement of the present invention, the wooden bottom plate is a paulownia bottom plate.
[0017] As a further improvement of the present invention, the electrolyte slurry comprises nano-scale gas-phase silica colloidal liquid, PbCl2, HCl, NaCl and water.
[0018] The present invention also discloses a method for preparing a micro lead-based solid non-polarizable electrode, comprising:
[0019] preparing an electrolyte slurry;
[0020] The electrolyte slurry is injected into the shell and filled in the upper cavity and the lower cavity, and the shell is divided into the upper cavity and the lower cavity by the diaphragm;
[0021] Inserting an anode wire into the upper cavity of the shell and connecting it to a test instrument via a wire;
[0022] The bottom of the shell is sealed with a wooden bottom plate, and finally a miniature lead-based solid non-polarized electrode is obtained.
[0023] As a further improvement of the present invention, the preparation of the electrolyte slurry comprises:
[0024] Step a, preparing fumed silica mother liquor: adding deionized water 4 to 6 times the weight of fumed silica into a stirring tank, gradually adding the formulated amount of fumed silica while stirring, and continuing to stir for 10 to 60 minutes after all the fumed silica is added; wherein the stirring tank has a stirring and cutting function and the rotation speed is greater than 3000r / min;
[0025] Step b, adding the solution in step a to a formulated amount of polyacrylamide, and continuing stirring for 10 to 60 minutes to prepare a fumed silica colloidal liquid;
[0026] Step c, mixing 0.1-100 g of PbCl2, 0-0.5 g of HCl, 0.1-10 kg of NaCl and water, and stirring by electromagnetic stirring until uniform to obtain a mixed solution; wherein the electromagnetic stirring speed is 10-100 r / min, and the stirring time is 0.5-2 h;
[0027] Step d, mixing the gas-phase silica colloidal liquid prepared in step b with the mixed solution prepared in step c and stirring them together by electromagnetic stirring until they are uniform, the electromagnetic stirring speed is 10 to 100 r / min, and the stirring time is 24 to 48 hours. The uniform colloid finally obtained is the electrolyte slurry.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention applies nano-scale fumed silica to the electrolyte, applies a polypropylene ion membrane to the structure, optimizes and modifies the electrolyte and the overall structure, makes the overall structure more suitable for miniaturized electrodes, and obtains a high-precision solid non-polarizable electrode that can be used stably for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A schematic diagram of the structure of a miniature lead-based solid non-polarizable electrode disclosed in one embodiment of the present invention;
[0031] Figure 2 for Figure 1 A top view of
[0032] Figure 3 This is a curve diagram of the change of polarization potential difference within 60 hours for Example 1, Example 2 and the comparative example disclosed in an embodiment of the present invention.
[0033] In the figure:
[0034] 1. Wire; 2. Fixing cap; 3. Wiring hole; 4. Shell; 5. Anode wire; 6. Electrolyte slurry; 7. Polypropylene diaphragm; 8. Paulownia base plate. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0037] like Figure 1 , 2 As shown, the present invention provides a miniature lead-based solid non-polarizable electrode, comprising: a conductor 1, a fixing cap 2, a wiring hole 3, a shell 4, an anode wire 5, an electrolyte slurry 6, a polypropylene diaphragm 7, and a paulownia wood bottom plate 8; wherein:
[0038] The shell 4 of the present invention is used as an electrode shell, which is a polypropylene shell made by 3D printing; the shell 4 has a top opening and a bottom opening, and the middle part of the shell 4 is divided into an upper cavity and a lower cavity by a diaphragm, and the upper cavity and the lower cavity are filled with electrolyte slurry 6, and it is confirmed that the electrolyte slurry completely fills the electrode shell cavity; wherein the diaphragm is a polypropylene diaphragm 7 with uniform pores, and the upper and lower layers of electrolyte slurry in the shell are separated by using the polypropylene diaphragm with uniform and stable pores, so that as little Pb in the upper cavity as possible is contained. 2+It exchanges with the conductive part of the lower part, and isolates the upper and lower parts through a diaphragm to avoid excessive local changes in electrolyte concentration, thereby maintaining a relatively long-term stability of the electrolyte; among them, the porosity of the polypropylene diaphragm is reasonably designed according to demand.
[0039] Further, the electrolyte slurry includes nano-sized fumed dioxide colloidal liquid, PbCl2, HCl, NaCl and water.
[0040] The top of the shell 4 of the present invention is provided with a fixing cap 2, which is a polypropylene fixing cap made by 3D printing; the fixing cap 2 is provided with a wiring hole 3 for the anode wire 5 to pass through, and the anode wire 5 is sealed on the wiring hole 3 by organic silicone, and one end of the anode wire 5 extends into the electrolyte slurry of the upper cavity, and the other end is connected to the external wire 1; wherein the anode wire 5 is a lead wire, the wire 1 is a copper wire, and the other end of the wire 1 is connected to the test instrument. Further, in order to ensure that the soft lead wire remains stable during use, the design of a long wiring hole is adopted in the present invention, so that even if the external wire vibrates, the internal lead wire can still maintain a stable position.
[0041] The bottom of the housing 4 of the present invention is provided with a wooden bottom plate, and the wooden bottom plate is preferably a paulownia bottom plate 8 ; the electrolyte slurry in the lower cavity is in contact with the external environment through the paulownia bottom plate 8 .
[0042] The present invention provides a method for preparing a miniature lead-based solid non-polarizable electrode, comprising:
[0043] Prepare electrolyte slurry and inject the electrolyte slurry into the shell; insert an anode wire into the upper cavity of the shell and connect it to a test instrument through a wire; use a wooden bottom plate to seal the bottom of the shell, and finally obtain a miniature lead-based solid non-polarized electrode.
[0044] The electrolyte slurry is prepared, comprising:
[0045] Step a, preparing fumed silica mother liquor: adding deionized water 4 to 6 times the weight of fumed silica to a stirring tank, gradually adding the formulated amount of fumed silica while stirring, and continuing to stir for 10 to 60 minutes after all the fumed silica is added; wherein the stirring tank has a stirring and cutting function and the rotation speed is greater than 3000 r / min;
[0046] Step b, adding the solution in step a to a formulated amount of polyacrylamide, and continuing stirring for 10 to 60 minutes to prepare a fumed silica colloidal liquid;
[0047] Step c, mixing 0.1-100 g of PbCl2, 0-0.5 g of HCl, 0.1-10 kg of NaCl and water, and stirring by electromagnetic stirring until uniform to obtain a mixed solution; wherein the electromagnetic stirring speed is 10-100 r / min, and the stirring time is 0.5-2 h;
[0048] Step d, mixing the gas-phase silica colloidal liquid prepared in step b with the mixed solution prepared in step c and stirring them together by electromagnetic stirring until they are uniform, the electromagnetic stirring speed is 10 to 100 r / min, and the stirring time is 24 to 48 hours. The uniform colloid finally obtained is the electrolyte slurry.
[0049] Example
[0050] Example 1
[0051] Accurately weigh 20 ml of deionized water, 0.8 g of PbCl2 powder and 20 g of NaCl powder, and mix them evenly by magnetic stirring at a mixing temperature of 25°C for 2 hours. Then add 10% HCl solution, adjust the pH of the mixed solution to 3.0, and continue mixing for 2 hours. Weigh 4 g of nano-SiO2 powder and add it to the original mixed solution. Stir vigorously for 5 hours at a mixing temperature of 25°C until it becomes a uniform slurry-like liquid, which is the final electrolyte slurry. Inject the electrolyte into Figure 1 The electrode shell is placed in the reactor and sealed with a paulownia plug to finally obtain a miniaturized high-precision solid-state non-polarizable electrode 1.
[0052] Example 2
[0053] Accurately weigh 50ml of deionized water, 2g of PbCl2 powder and 45g of NaCl powder, and mix them evenly by magnetic stirring at a mixing temperature of 25°C for 5h, then add 10% HCl solution, adjust the pH of the mixed solution to 2.8, and continue mixing for 2h. Weigh 4g of nano-SiO2 powder and 1g of polyacrylamide powder, add them to the original mixed solution, stir vigorously for 15h, and mix at a mixing temperature of 25°C until it becomes a uniform slurry-like liquid, which is the final electrolyte slurry. Inject the electrolyte into Figure 1 The electrode shell is sealed with a paulownia plug to finally obtain a miniaturized high-precision solid-state non-polarized electrode 2.
[0054] Comparative Example
[0055] Accurately weigh 50ml of deionized water, 2g of PbCl2 powder and 45g of NaCl powder, and mix them evenly by magnetic stirring at a mixing temperature of 25°C for 5h, then add a 10% HCl solution, adjust the pH of the mixed solution to 3.0, and continue mixing for 2h. Weigh 20g of kaolin and add it to the original mixed solution, stir and mix for 8h at a mixing temperature of 25°C until it becomes a uniform slurry-like liquid, which is the final electrolyte slurry. The electrode structure refers to the structure in the paper (Gilbert Petiau, Second Generation of Lead-lead Chloride Electrodes, Pure appl. geophys. 157 (2000) 357-382.) to make a general-sized ordinary kaolin-based electrolyte non-polarized electrode.
[0056] test:
[0057] Test Method
[0058] Using saturated sodium chloride solution as the test environment, the polarization potential difference of two electrodes with the same electrolyte, the range change curve within 60 hours and the internal impedance test were tested. The test results are shown in Table 1 and Figure 3 As shown in Table 1 and Figure 3 It can be seen that the embodiments all perform well in terms of performance, with the initial range being less than 0.4 mV, and the range drift value not exceeding 0.15 mV during the 60-hour test, which is fully in line with the application of short-term laboratory simulation experiments. In addition, the internal impedance of the embodiment is 1.57 Ω / m, which is lower than 2.60 Ω / m of the comparative example, which shows that the electrode of the embodiment has better conductivity and the test accuracy is higher than that of the comparative example.
[0059] Table 1
[0060] Electrode Group Range mV Range change within 30h mV Range change within 60h mV Electrode resistance density Ω / m Example 1 0.358 0.148 0.249 1.57 Example 2 0.393 0.094 0.175 1.59 Comparative Example 23.367 16.354 20.626 2.60
[0061] The advantages of the present invention are:
[0062] 1. The present invention prepares colloids by using nano-scale fumed silica particles with a lower water loss rate, replacing the currently commonly used viscous materials such as kaolin or gypsum; the electrolyte slurry prepared by using nano-scale fumed silica colloids has better component uniformity and ion conductivity, and improves the stability of non-polarized electrodes from the electrolyte aspect.
[0063] 2. The present invention uses a polypropylene diaphragm to replace the small channel-type spacer previously used in the market, thereby reducing the problem of electrolyte component concentration when the electrode is in use and improving the stability of the non-polarized electrode from a structural aspect.
[0064] 3. The present invention miniaturizes the non-polarizable electrode so that the electrode can be used for indoor miniaturization and short-term high-precision simulation conditions; it solves the disadvantage that ordinary electrodes are large in size and unsuitable for laboratory model simulation.
[0065] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A miniature lead-based solid non-polarizable electrode, characterized in that: include: case; The middle part of the shell is divided into an upper cavity and a lower cavity by a diaphragm, and the upper cavity and the lower cavity are both filled with electrolyte slurry; The diaphragm is a polypropylene diaphragm with uniform pores; The electrolyte slurry comprises nano-scale fumed dioxide colloidal liquid, PbCl2, HCl, NaCl and water; A fixing cap is provided on the top of the shell, and an anode wire is passed through the fixing cap. One end of the anode wire extends into the electrolyte slurry of the upper cavity, and the other end is connected to an external wire. A wooden bottom plate is provided at the bottom of the shell, and the electrolyte slurry in the lower cavity is in contact with the external environment through the wooden bottom plate.
2. The miniature lead-based solid non-polarizable electrode according to claim 1, characterized in that: The shell and the fixing cap are both polypropylene components.
3. The miniature lead-based solid non-polarizable electrode according to claim 1, characterized in that: The fixing cap is provided with a wiring hole for the anode wire to pass through, and the anode wire is sealed on the wiring hole by organic silica gel.
4. The miniature lead-based solid non-polarizable electrode according to claim 3, characterized in that: The wiring hole is a long wiring hole with a preset length.
5. The miniature lead-based solid non-polarizable electrode according to claim 1, characterized in that: The anode wire is a lead wire, the conductor is a copper conductor, and the other end of the conductor is connected to a testing instrument.
6. The miniature lead-based solid non-polarizable electrode according to claim 1, characterized in that: The wooden bottom plate is a paulownia wood bottom plate.
7. A method for preparing a miniature lead-based solid non-polarizable electrode as claimed in any one of claims 1 to 6, characterized in that: include: preparing an electrolyte slurry; The electrolyte slurry is injected into the shell and filled in the upper cavity and the lower cavity, and the shell is divided into the upper cavity and the lower cavity by the diaphragm; Inserting an anode wire into the upper cavity of the shell and connecting it to a test instrument via a wire; The bottom of the shell is sealed with a wooden bottom plate, and finally a miniature lead-based solid non-polarized electrode is obtained.
8. The preparation method according to claim 7, characterized in that: The preparation of electrolyte slurry comprises: Step a, preparing fumed silica mother liquor: adding deionized water 4 to 6 times the weight of fumed silica into a stirring tank, gradually adding the formulated amount of fumed silica while stirring, and continuing to stir for 10 to 60 minutes after all the fumed silica is added; wherein the stirring tank has a stirring and cutting function and the rotation speed is greater than 3000r / min; Step b, adding the solution in step a to a formulated amount of polyacrylamide, and continuing stirring for 10 to 60 minutes to prepare a fumed silica colloidal liquid; Step c, mixing 0.1-100 g of PbCl2, 0-0.5 g of HCl, 0.1-10 kg of NaCl and water, and stirring by electromagnetic stirring until uniform to obtain a mixed solution; wherein the electromagnetic stirring speed is 10-100 r / min, and the stirring time is 0.5-2 h; Step d, mixing the gas-phase silica colloidal liquid prepared in step b with the mixed solution prepared in step c and stirring them together by electromagnetic stirring until they are uniform, the electromagnetic stirring speed is 10 to 100 r / min, and the stirring time is 24 to 48 hours. The uniform colloid finally obtained is the electrolyte slurry.
Citation Information
Patent Citations
Electrolyte, preparation method and use of electrolyte
CN105785449A
High accuracy non polarizing electrode
CN205643732U
Miniature lead-based solid non-polarized electrode
CN213398932U
Cited By
Ultra-stable non-polarized electrode and preparation method thereof
CN114791624A
A superstable non-polarizable electrode and preparation method thereof
CN114791624B
Preparation method of non-polarized electrode of indoor sand box model and electrode
CN115793061A